2006
DOI: 10.1016/j.trstmh.2005.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Underestimation of snakebite mortality by hospital statistics in the Monaragala District of Sri Lanka

Abstract: Estimates of snakebite mortality are mostly based on hospital data, although these may considerably underestimate the problem. In order to determine the accuracy of hospital-based statistics, data on snakebite mortality in all hospitals in the Monaragala District of Sri Lanka were compared to data on snakebite as the certified cause of death for the district, for the 5-year period between 1999 and 2003. Data were cross-checked in a sample of hospitals and divisional secretariats within the district. Hospital s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 3 publications
4
53
0
Order By: Relevance
“…However, existing epidemiological data remain fragmented and the true impact of snake bites is very likely to be underestimated. Surveys in rural Sri Lanka showed that hospital data record less then half of the deaths due to snakebite [9]–[11]. In Nepal, a review of district hospital records showed that national figures underestimated the incidence of snake bite by one order of magnitude [12].…”
Section: Epidemiologymentioning
confidence: 99%
“…However, existing epidemiological data remain fragmented and the true impact of snake bites is very likely to be underestimated. Surveys in rural Sri Lanka showed that hospital data record less then half of the deaths due to snakebite [9]–[11]. In Nepal, a review of district hospital records showed that national figures underestimated the incidence of snake bite by one order of magnitude [12].…”
Section: Epidemiologymentioning
confidence: 99%
“…However, these data, based on hospital records, underestimate the true extent of the problem. 2,3 More than 100 terrestrial snake species inhabit Sri Lanka, but only six are medically important: Indian cobra ( Naja naja ), common and Sri Lankan kraits ( Bungarus caeruleus and B. ceylonicus ), Russell's viper ( Daboia russelii ), saw-scaled viper ( Echis carinatus ), and hump-nosed pit viper ( Hypnale hypnale ). 4,5 Three other vipers, H. nepa , H. walli , and Trimeresurus trigonocephalus , bite rarely and with negligible consequences as do some mildly venomous colubrids.…”
Section: Introductionmentioning
confidence: 99%
“…The actual figures are likely to be much higher than these estimates. A study in a rural Sri Lankan community found that nearly two-thirds of snakebite related deaths are not reported in hospital-based data [3]. A nationally representative survey in Bangladesh suggested that incidence of snakebite is much higher than previously estimated [4].…”
Section: Introductionmentioning
confidence: 94%